Diversity of Family Farming Around the World Existence, Transformations and Possible Futures of Family Farms (Springer Netherlands, 2018)
In contemporary times where farming models are challenged through deep transformations of agricultural organizations and markets, this books proposes a new visit of the diversity of family forms of production to explore their current transformations all over the world. By adopting a comprehensive perspective it allows bringing together several dimensions often studied separately: linkages with markets, territorial development, labour mobility through migrations and livelihood strategies, farms' autonomy, and food security, as well as the many ways of collective action and the role of public policies. The book relies on 18 case studies in the five continents. All were driven with a single and original methodological framework, inspired by the Sustainable Rural Livelihoods. The SRL initial framework was reshaped and adapted to allow each author to fine-tune "what makes family", to understand family labour adaptations to their environment, and to align them with territorial dynamics and public policies in each national situation. Co-written by a network of researchers, this book deepens scientific knowledge on family farming around the world, and at the same time it contributes to test and improve a methodological framework adapted to analyse and of observe rural dynamics. It is dedicated to researchers, teachers and students, agronomists, economists, geographers, sociologists and historians but also experts and practitioners in agricultural and rural development. More widely, NGOs and any citizen willing to understand the family farming's issues in different social contexts, should also find interest in reading it.